Perspectives on Public Policy in Societal-Environmental Crises What the Future Needs from History - Izdebski, Adam; Haldon, John; Filipkowski, Piotr (Risk, Systems and Decisions, 2022)
This is an open access book. Histories we tell never emerge in a vacuum, and history as an academic discipline that studies the past is highly sensitive to the concerns of the present and the heated debates that can divide entire societies. But does the study of the past also have something to teach us about the future? Can history help us in coping with the planetary crisis we are now facing? By analyzing historical societies as complex adaptive systems, we contribute to contemporary thinking about societal-environmental interactions in policy and planning and consider how environmental and climatic changes, whether sudden high impact events or more subtle gradual changes, impacted human responses in the past. We ask how societal perceptions of such changes affect behavioral patterns and explanatory rationalities in premodernity, and whether a better historical understanding of these relationships can inform our response to contemporary problems of similar nature and magnitude, such as adapting to climate change.